In Vitro Assessment of Compression Patterns Using Different Methods to Achieve Interfragmentary Compression during Tibial Plateau Levelling Osteotomy - Alvarez, Rodrigo; Motta, Claudio; Miraldo, Diogo (Veterinary and Comparative Orthopaedics and Traumatology, 2024)
Objectives The aim of this study was to evaluate and characterize different methods to achieve interfragmentary compression during tibial plateau levelling osteotomy (TPLO).Study Design TPLO was performed in 20 canine tibia models (Sawbones, Vashon, Washington, United States) using 3D-printed guides for standardization. Interfragmentary compression was assessed using pressure-sensitive films (Prescale, Fujifilm, Atherstone, United Kingdom). Seven compression methods were tested: (1) Kern bone holding forceps clamping the craniodistal aspect of the TPLO plate to the caudal aspect of the tibia (K); (2) using the distal TPLO plate dynamic compression hole (P); (3) pointed bone reduction forceps engaging the caudal aspect of the proximal bone fragment and the cranial aspect of the tibial crest (F); (4) K + P; (5) K + F; (6) F + P; and (7) K + F + P. Five measurements were obtained for each method, and each bone model was used for two measurements (single method, ± plate). The interfragmentary surface was digitalized and divided into quadrants for standardization and pixel density calculation: Q1, craniomedial; Q2, craniolateral; Q3, caudomedial; and Q4, caudolateral. One-way analysis of variance (ANOVA) and post hoc tests were used for statistical analysis.Results Mean pressures per quadrant differed significantly between methods (p < 0.001). Methods K, F, and P produced more craniomedial, craniolateral, and caudal compression, respectively. Method K resulted in loss of caudal compression (p < 0.001). Method F + P provided the most even distribution of high interfragmentary compression forces. The addition of method K to this construct (K + F + P) marginally increased cranial compression (p = 0.189 for Q1; p < 0.001 for Q2), but reduced compression caudally (p < 0.001).Conclusion Method F + P provided more even interfragmentary compression. If method K were used, then combined use with method F + P would be recommended.
Keywords: interfragmentary compression; tibial plateau leveling osteotomy; compression methods; pressure-sensitive film